Preparation method and application of carboxylated polyamide-amine / amorphous calcium phosphate-decyl methacrylate phosphate nanocomposite
By preparing carboxylated polyamide-amine/amorphous calcium phosphate-decyl phosphate nanocomposite in ethanol solution, the problem of easy agglomeration of existing composites in aqueous solution is solved, and the resin adhesive is realized The stability and permeability in the process promote the remineralization of dentin collagen fibers, enhance the bonding strength and anti-aging properties.
Patent Information
- Application Number
- CN202411371450.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing carboxylated polyamide-amine/amorphous calcium phosphate nanocomposites are prone to agglomeration in aqueous solution, lose their nano size, are inconvenient to use and are difficult to dissolve in the solvent used in resin adhesives, which limits its clinical application. .
By preparing carboxylated polyamide-amine/amorphous calcium phosphate-decyl phosphate nanocomplex in ethanol solution, the lipophilic end structure of decyl phosphate methacrylate increases the lipophilic solubility of the complex, and Maintaining a stable nanoscale in ethanol, combining the inhibitory effect of hydroxyapatite, induces remineralization of demineralized dentin collagen fibers.
The composite has been maintained at a stable nanoscale in ethanol solution for a long time, has good permeability, can effectively induce the remineralization of demineralized dentin collagen fibers, and improve the stability and anti-aging performance of the resin-dentin bonding interface. .
Smart Images

Figure BDA0005067683770000031 
Figure BDA0005067683770000101 
Figure HDA0005067683790000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of demineralized dentin collagen fiber remineralization at a resin bonding interface, in particular to a preparation method and application of a polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite. Background Art
[0002] Resin fillings and restorations in oral clinics mainly rely on bonding for retention. Dentin bonding is to demineralize the dentin surface through acid etching to form a bare collagen fiber network, and then use the resin monomer in the adhesive to replace the water in the fiber network and cross-link with the collagen fibers to form a resin-collagen mixed layer to form a strong bonding interface. However, in the above bonding process, the resin monomer is not enough to completely replace the water in the collagen fiber network, so that part of the collagen fibers in the bonding interface are exposed to the water environment, which is easily degraded under the action of various endogenous enzymes, resulting in the destruction of the bonding interface. Promoting the bionic remineralization of these exposed demineralized collagen fibers, so that they are protected by minerals both inside and outside, and restoring their mechanical properties can enhance the stability of the resin-dentin bonding interface. This is a method that has emerged in recent years and can fundamentally avoid the above-mentioned defects of dentin bonding. Studies have found that carboxylated polyamide-amine has the function of stabilizing amorphous phase mineralization precursor amorphous calcium phosphate, such as the paper "Research on Carboxylated Polyamide-amine / Amorphous Calcium Phosphate Magnesium Induced Collagen Fiber Remineralization" (Yan Kaiqi, Huang Xiaoman, Huang Jingxian, Xie Fangfang, Journal of Guangxi Medical University, 2023, 40(2): 221-227.) disclosed: Preliminary experiments synthesized a nano-sized carboxylated polyamide-amine / amorphous calcium phosphate nanocomposite containing magnesium, which confirmed its ability to induce human dentin collagen fiber remineralization. However, the complex is synthesized in an aqueous solution, and it is easy to agglomerate over time, losing its nanometer size, and can only be stored in a freeze-dried powder state. It is re-prepared with water when used, which is inconvenient to use and has a large loss. In addition, the complex is difficult to dissolve in the ethanol or acetone solvents used by the resin adhesive, which limits its further application in clinical replacement of existing resin adhesives.
[0003] Therefore, further in-depth research on the magnesium-containing nano-sized carboxylated polyamide-amine / amorphous calcium phosphate nanocomposite so that it can be better preserved for a long time and soluble in the solvent used by the resin adhesive is of great significance for its better clinical replacement of existing resin adhesives. Summary of the invention
[0004] The invention provides a preparation method and application of a polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite, which can maintain a stable nanometer size in an ethanol solution for a long time, has good permeability, and can induce the remineralization of demineralized dentin collagen fibers.
[0005] To achieve the above object, the technical solution of the present invention is:
[0006] A method for preparing a carboxylated polyamidoamine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite comprises the following steps:
[0007] (1) mixing a carboxylated polyamide-amine aqueous solution and a soluble magnesium salt aqueous solution, allowing the mixture to stand for 4 to 10 hours, adding a soluble calcium salt, continuing to mix the mixture, allowing the mixture to stand for 4 to 10 hours, and then adding anhydrous ethanol, or anhydrous ethanol and distilled water, to obtain an ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium;
[0008] (2) dissolving decyl methacrylate phosphate in an ethanol solution, adding a phosphoric acid solution or a soluble phosphate solution, and mixing well to obtain a phosphorus solution;
[0009] (3) Evenly mixing the ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium with the phosphorus solution, wherein the molar ratio of calcium ions to phosphate ions is 2 to 1:1, and stirring or shaking the mixture for 20 to 60 minutes to obtain a polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite.
[0010] Preferably, in the ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium, the concentration of carboxylated polyamide-amine is 0.10 to 1.50 mmol / L, and the concentration of Mg is 0.10 to 1.50 mmol / L. 2+ The concentration of Ca is 0.05~0.50mmol / L, 2+ The concentration is 1~20mmol / L.
[0011] Preferably, in the ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium, carboxylated polyamide-amine, Mg 2+ , Ca 2+ The molar ratio is 0.5~5:1:20~50.
[0012] Preferably, the volume percentage of ethanol in the ethanol mixed solution containing magnesium, carboxylated polyamide-amine and amorphous calcium and / or in the phosphorus solution is 40-60%.
[0013] Preferably, in the phosphorus solution, PO4 3- The concentration of is 0.5~12.0mmol / L, and the concentration of decyl methacrylate phosphate is 0.5~12.0mmol / L.
[0014] Preferably, in the phosphorus solution, decyl methacrylate phosphate and PO4 3- The molar ratio is 1~10:1~10.
[0015] Preferably, in step (3), the reaction temperature is 8-15°C.
[0016] Preferably, step (1) is specifically as follows: 0.8-12 mmol / L of a carboxylated polyamide-amine aqueous solution and 10-100 mmol / L of a magnesium chloride aqueous solution are vortex mixed at a volume ratio of 15-35:1, and allowed to stand for 4-10 hours. Then, 10-100 mmol / L of a calcium chloride aqueous solution with a volume of 30-50 times that of the magnesium chloride aqueous solution is added, and vortex mixed, and allowed to stand for 4-10 hours. Then, 30-50 times the volume of the magnesium chloride aqueous solution is added with distilled water and 80-120 times the volume of the magnesium chloride aqueous solution is added with anhydrous ethanol, and vortex mixed to obtain an ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium.
[0017] Preferably, step (2) specifically comprises: preparing 0.5-13.0 mmol / L of 40-60 vol% ethanol solution of decyl methacrylate phosphate, adding concentrated phosphoric acid to make the concentration of phosphoric acid 0.5-12.0 mmol / L, vortex mixing, and obtaining the phosphorus solution.
[0018] The above-mentioned decyl methacrylate phosphate, also known as 10-(2-methacryloyloxy) monodecyl phosphate, has the chemical formula:
[0019]
[0020] The present invention further provides the application of the preparation method of the above-mentioned polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite in inducing collagen fiber biomimetic mineralization and resin bonding.
[0021] The present invention utilizes carboxylated polyamide-amine and magnesium ions to stabilize the amorphous calcium phosphate, a mineralization precursor, to inhibit the amorphous calcium phosphate from aggregating and mineralizing to form hydroxyapatite before entering the collagen fibers, so as to facilitate the induction of remineralization in the demineralized dentin collagen fibers, and simultaneously introduces decyl methacrylate phosphate to increase the fat solubility of the composite by utilizing the structural characteristics of its lipophilic end. Experiments have confirmed that the nanocomposite introduced with decyl methacrylate phosphate can maintain a stable nanometer size in an ethanol solution for a long time, and has good permeability, and can induce the remineralization of the demineralized dentin collagen fibers. Application experiments of dentin bonding have also confirmed that the polyamide-amine / amorphous calcium phosphate-decyl methacrylate phosphate nanocomposite prepared by the present invention can be used as an additional primer, can effectively improve the bonding strength and has better anti-aging performance.
[0022] The present invention improves the carboxylated polyamide-amine / amorphous amorphous calcium phosphate material, which can not only promote the bionic remineralization of exposed demineralized dentin collagen fibers, so that the inside and outside are protected by minerals and the mechanical properties are restored, but also can be used for resin bonding of dentin in clinical practice to enhance the bonding strength and anti-aging performance of the bonding and extend the life of the resin restoration. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A is the general view of PAMAM-COOH / ACMP (freshly prepared) in Example 1, Figure 1 B is a general view of PAMAM-COOH / ACMP-MDP (freshly prepared) of Example 1, Figure 1 C is the general view of PAMAM-COOH / ACMP of Example 1 (after storage for 60 days). Figure 1 D is the general view of PAMAM-COOH / ACMP-MDP of Example 1 (after storage for 60 days).
[0024] Figure 2 A is the Fourier transform infrared spectra of PAMAM-COOH / ACMP (freshly prepared) of Comparative Example 1 and PAMAM-COOH / ACMP-MDP (freshly prepared) of Example 1, Figure 2 B is the Fourier transform infrared spectra of PAMAM-COOH / ACMP of Comparative Example 1 (after 60 days of storage) and PAMAM-COOH / ACMP-MDP of Example 1 (after 60 days of storage).
[0025] Figure 3 A is the X-ray diffraction pattern of PAMAM-COOH / ACMP (freshly prepared) of Comparative Example 1 and PAMAM-COOH / ACMP-MDP (freshly prepared) of Example 1, Figure 3 B is the X-ray diffraction pattern of PAMAM-COOH / ACMP of Comparative Example 1 (after 60 days storage) and PAMAM-COOH / ACMP-MDP of Example 1 (after 60 days storage).
[0026] Figure 4 TEM images of PAMAM-COOH / ACMP of Comparative Example 1 and PAMAM-COOH / ACMP-MDP of Example 1; Figure 4 A is the transmission electron microscopy image of PAMAM-COOH / ACMP (freshly prepared) (scale bars 500nm, 100nm), Figure 4 B is the transmission electron microscopy image of PAMAM-COOH / ACMP-MDP (freshly prepared) (scale bars 500nm, 100nm), Figure 4 C is the transmission electron microscopy image of PAMAM-COOH / ACMP (after 60 days of storage) (scale bars 500nm, 100nm), Figure 4 D is the transmission electron microscopy image of PAMAM-COOH / ACMP-MDP (after storage for 60 days) (scale bars: 500 nm, 100 nm).
[0027] Figure 5It is a particle size analysis diagram of PAMAM-COOH / ACMP of Comparative Example 1 (freshly prepared and stored for 60 days) and PAMAM-COOH / ACMP-MDP of Example 1 (freshly prepared and stored for 60 days).
[0028] Figure 6 is the STEM-EDX-mapping test result of PAMAM-COOH / ACMP of Comparative Example 1 and PAMAM-COOH / ACMP-MDP of Example 1; Figure 6 A is the energy spectrum analysis diagram of PAMAM-COOH / ACMP (freshly prepared), Figure 6 B is the energy spectrum analysis diagram of PAMAM-COOH / ACMP-MDP (freshly prepared), Figure 6 C is the energy spectrum analysis diagram of PAMAM-COOH / ACMP (after 60 days of storage), Figure 6 D is the energy spectrum analysis diagram of PAMAM-COOH / ACMP-MDP (after 60 days of storage). From left to right in the figure are high-angle annular dark field imaging, element distribution overlay diagram, calcium element distribution diagram, phosphorus element distribution diagram, magnesium element distribution diagram, and nitrogen element distribution diagram.
[0029] Figure 7 These are the CLSM observation results of the remineralization of the longitudinal sections of dentin after mineralization induction in the blank control group, ACP group, MDP group, PAMAM-COOH / ACMP group, and PAMAM-COOH / ACMP-MDP group in experiment (1). The left column of images is the low-power field of view (×400), and the right column of images is the high-power field of view (×1000).
[0030] Figure 8 Figure 1 is the scanning electron microscopy observation result of the longitudinal section of the completely demineralized dentin surface in experiment (2); Figures A1-A5 are the test result of the blank control group: Figures A2 and A3 are the white box area in A1, and Figures A4 and A5 are the black box area in A1. The magnification of Figures A2 and A4 is 25,000, and the magnification of Figures A3 and A5 is 50,000 ( Figure 8 B1-5, Figure 8 C1-5, Figure 8 D1-5, Figure 8 E1-5 are arranged in the same way); B1-B5 are test result diagrams of the ACP group, C1-C5 are test result diagrams of the MDP group, D1-D5 are test result diagrams of the PAMAM-COOH / ACMP group (Comparative Example 1), and E1-E5 are test result diagrams of the PAMAM-COOH / ACMP-MDP group (Example 1).
[0031] Fig. 9Figure 1 is the transmission electron microscopy observation result of completely demineralized dentin in experiment (2); Figures A1 and A2 are the test results of the blank control group: A1 is a low-power field of view (×3000), and A2 is an enlarged view of the white box area in Figure A1 ( Fig. 9 B1-2, Fig. 9 C1-2, Fig. 9 D1-2, Fig. 9 E1-2 are arranged in the same way); B1-B2 are test result diagrams of the ACP group, C1-C2 are test result diagrams of the MDP group, D1-D2 are test result diagrams of the PAMAM-COOH / ACMP group (Comparative Example 1), and E1-E2 are test result diagrams of the PAMAM-COOH / ACMP-MDP group (Example 1).
[0032] Fig.10 This is a picture of collagen fibers mineralized by PAMAM-COOH / ACMP-MDP group (×50000). DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A method for preparing a carboxylated polyamidoamine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite comprises the following steps:
[0036] (1) 625 μL of 5 mmol / L carboxylated polyamide-amine aqueous solution and 25 μL of 50 mmol / L magnesium chloride aqueous solution were vortexed and allowed to stand for 8 h. Then, 975 μL of 50 mmol / L calcium chloride aqueous solution were added and vortexed and allowed to stand for 8 h. Then, 875 μL of distilled water and 2.5 mL of anhydrous ethanol were added and vortexed to obtain a 0.25 mmol / L solution of magnesium chloride. 2+ , 0.625mmol / L carboxylated polyamidoamine and 9.75mmol / L amorphous calcium in ethanol and stored at 4°C.
[0037] (2) Prepare a 6 mmol / L 50 vol% ethanol solution of decyl methacrylate phosphate, add 85% concentrated phosphoric acid, and make PO4 3- The concentration was 6mmol / L, vortex mixed to obtain phosphorus solution, and stored at 4℃;
[0038] (3) The ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium was vortex-mixed with the phosphorus solution in a volume ratio of 1:1, and the mixture was placed in a shaker at 10° C. and continued to react for 30 minutes to obtain a polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite (PAMAM-COOH / ACMP-MDP).
[0039] Example 2
[0040] A method for preparing a carboxylated polyamidoamine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite comprises the following steps:
[0041] (1) 625 μL of 6 mmol / L carboxylated polyamide-amine aqueous solution and 25 μL of 52 mmol / L magnesium chloride aqueous solution were vortexed and allowed to stand for 10 h. Then, 975 μL of 52 mmol / L calcium chloride aqueous solution were added and vortexed and allowed to stand for 8 h. Then, 875 μL of distilled water and 2.5 ml of anhydrous ethanol were added and vortexed to obtain a 0.26 mmol / L solution of magnesium chloride. 2+ , 0.75mmol / L carboxylated polyamidoamine and 10.14mmol / L amorphous calcium in ethanol and stored at 4°C.
[0042] (2) Prepare a 6 mmol / L 55 vol% ethanol solution of decyl methacrylate phosphate, add 85% concentrated phosphoric acid, and make PO4 3- The concentration was 6mmol / L, vortex mixed to obtain phosphorus solution, and stored at 4℃;
[0043] (3) The ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium was vortex-mixed with the phosphorus solution in a volume ratio of 1:1, and the mixture was placed in a shaker at 10° C. and continued to react for 40 minutes to obtain a polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite.
[0044] Example 3
[0045] A method for preparing a carboxylated polyamidoamine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite comprises the following steps:
[0046] (1) 625 μL of 5 mmol / L carboxylated polyamide-amine aqueous solution and 25 μL of 50 mmol / L magnesium chloride aqueous solution were vortexed and allowed to stand for 8 h. Then, 975 μL of 50 mmol / L calcium chloride aqueous solution were added and vortexed and allowed to stand for 8 h. Then, 875 μL of distilled water and 2.5 mL of anhydrous ethanol were added and vortexed to obtain a 0.25 mmol / L solution of magnesium chloride. 2+, 0.625mmol / L carboxylated polyamidoamine and 9.75mmol / L amorphous calcium in ethanol and stored at 4°C.
[0047] (2) Prepare a 50 vol% ethanol solution of 5 mmol / L decyl methacrylate phosphate and add 85% concentrated phosphoric acid to make PO4 3- The concentration was 5mmol / L, vortex mixed to obtain phosphorus solution, and stored at 4℃;
[0048] (3) The ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium was vortex-mixed with the phosphorus solution in a volume ratio of 1:1, and the mixture was placed in a shaker at 10° C. and continued to react for 20 minutes to obtain a polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite.
[0049] Comparative Example 1
[0050] (1) 625 μL of 5 mmol / L carboxylated polyamide-amine aqueous solution and 25 μL of 50 mmol / L magnesium chloride aqueous solution were vortexed and allowed to stand for 8 h. Then, 975 μL of 50 mmol / L calcium chloride aqueous solution were added and vortexed and allowed to stand for 8 h. Then, 875 μL of distilled water and 2.5 mL of anhydrous ethanol were added and vortexed to obtain a 0.25 mmol / L solution of magnesium chloride. 2+ , 0.625mmol / L carboxylated polyamidoamine and 9.75mmol / L amorphous calcium in ethanol and stored at 4°C.
[0051] (2) Add 85% concentrated phosphoric acid to a 50 vol% ethanol solution to make the concentration of phosphoric acid 6 mmol / L, vortex mix to obtain phosphorus solution, and store at 4°C.
[0052] (3) The ethanol mixture containing magnesium, carboxylated polyamidoamine and amorphous calcium and the phosphorus solution in the above step are vortex-mixed at a volume ratio of 1:1, placed in a shaking table at 10° C. to continue the reaction, taken out after 30 minutes, and stored at 4° C. To obtain a magnesium-containing carboxylated polyamidoamine / amorphous calcium phosphate (PAMAM-COOH / ACMP) ethanol solution.
[0053] Performance test
[0054] 1. Stability test
[0055] The physical and chemical properties of freshly prepared PAMAM-COOH / ACMP-MDP (Example 1) and PAMAM-COOH / ACMP (Comparative Example 1) after storage for 60 days were tested. Figure 1 A- Figure 1 As shown in D, both can maintain the original colorless clear liquid state. Analyze its chemical bond information, such as Figure 2 A and Figure 2 As shown in B, the freshly prepared PAMAM-COOH / ACMP-MDP and PAMAM-COOH / ACMP can be detected at a wavelength of 1080 cm -1 PO4 observed nearby 3- Characteristic peak, 1560cm -1 and 1651cm -1 The characteristic peaks of amide bond (-NH-CO-) and carbonyl group (-C=O) were observed near the PAMAM-COOH / ACMP-MDP at 1730 cm -1 The characteristic peak of carbonyl group (-C=O) of MDP was observed near the wavelength. After 60 days of storage, characteristic peaks of PAMAM-COOH / ACMP-MDP and PAMAM-COOH / ACMP were still observed near the corresponding wavelength, indicating that both can maintain good chemical stability. Figure 3 A and Figure 3 As shown in Figure B, whether it is freshly prepared PAMAM-COOH / ACMP-MDP, PAMAM-COOH / ACMP, or PAMAM-COOH / ACMP-MDP, PAMAM-COOH / ACMP after storage for 60 days, an independent large package peak unique to amorphous phase materials can be seen at 2θ=24°, indicating that both can maintain the amorphous phase state and have good stability.
[0056] Transmission electron microscopy was used to observe the microscopic morphology and particle size changes of the two. Figure 4 and Figure 5 As shown, Figure 4 In A, it can be seen that the particles of PAMAM-COOH / ACMP are quasi-spherical and well dispersed, but still have a slight tendency to aggregate and are not uniform in size. Under a high-power microscope, they show a quasi-spherical particle structure with an average particle size of 81.97±19.27nm. Figure 4 In B, it can be seen that the particles of PAMAM-COOH / ACMP-MDP have better dispersion and more consistent particle size. Under a high-power microscope, they appear to have a quasi-round particle structure with an average particle size of 49.69±6.47nm. Figure 4 C. Figure 4 D shows that PAMAM-COOH / ACMP and PAMAM-COOH / ACMP-MDP maintain similar round particle structures after 60 days of storage, with high particle dispersion and no agglomeration. No diffraction spots or diffraction rings were found in SEAD detection, indicating that they are all amorphous materials ( Figure 4 A, B, C, D upper right corner). Figure 4 and Figure 5It shows that the particle dispersion of PAMAM-COOH / ACMP-MDP is better and the particle size is more consistent. Under high magnification, it appears as a quasi-round particle structure. Its average particle size is 49.69±6.47nm, which is smaller than the average particle size of PAMAM-COOH / ACMP (81.97±19.27nm). It can maintain its original nanoparticle size after being stored for 60 days, and has good stability.
[0057] In addition, we also conducted STEM-EDX-mapping tests. The results are as follows: Figure 6 As shown, Figure 6 A and Figure 6 B shows that calcium and phosphorus are enriched in the particles of the PAMAM-COOH / ACMP and PAMAM-COOH / ACMP-MDP complexes, confirming that these particles are calcium-phosphorus clusters. A small amount of magnesium and nitrogen enrichment can also be seen in the particles. Figure 6 C and Figure 6 D shows that the composite particles after 60 days of storage are basically consistent with the results of the fresh configuration. These results indicate that the new mineralization system has good dispersion and can maintain nanometer size and has good stability.
[0058] 2. Induced mineralization simulation test
[0059] The experimental groups were set as a blank control group (50 vol% ethanol solution), an ACP group (amorphous calcium phosphate powder was added to 50 vol% ethanol at a concentration of 3 mg / mL), an MDP group (decyl methacrylate was added to 50% anhydrous ethanol at a concentration of 3 mmol / L), a PAMAM-COOH / ACMP group (synthesized according to the method of Comparative Example 1), and a PAMAM-COOH / ACMP-MDP group (synthesized according to the method of Example 1).
[0060] Experiment (1): The remineralization detection method is to use calcein fluorescence labeling technology to evaluate the remineralization effect of the surface of partially demineralized human dentin slices after mineralization induction. Utilizing the characteristic of calcein that it can bind to calcium ions, the newly formed mineralized products can show special yellow-green fluorescence under a laser scanning confocal fluorescence microscope, thereby distinguishing the newly formed from the original minerals. According to the grouping, 5 tooth slices in each group, each tooth was immersed in 0.5 ml of the fluorescent labeled solution of each group, and incubated in a constant temperature box at 37°C, 100% humidity, and light-proof conditions for 7 days. The dentin slices were taken out, rinsed with deionized water for 30 seconds, and then stored in deionized water for testing. The longitudinal section of the upper surface of the dentin slice was observed using a laser scanning confocal fluorescence microscope. Five high-power fields (×1000) of the dentin longitudinal section were randomly selected from the observation interface of each group of samples, and the depth of fluorescent label penetration was measured in 8 dentinal tubules randomly selected in each field. Each tubule was measured 3 times and the average value was taken. The statistical results of the penetration depth of dentinal tubules in each group were expressed in the form of x±S.
[0061] Experimental Results Figure 7 As shown in the figure, except for the blank control group and the MDP group, new mineral deposition can be seen on the surface of the other groups. Fluorescently labeled calcium ions can be seen penetrating deep into the dentinal tubules in both the PAMAM-COOH / ACMP group and the PAMAM-COOH / ACMP-MDP group. Compared with the control groups, not only new mineral deposition can be seen on the surface of the dentin after mineralization induction with the PAMAM-COOH / ACMP-MDP ethanol solution, but fluorescently labeled calcium ions also penetrate deep into the dentinal tubules, indicating that it can induce deep dentin remineralization. The depth of calcium ion penetration into the dentinal tubules in each group is shown in Table 1,
[0062] Table 1 Depth of calcium ion penetration into dentinal tubules in each group (x±S)
[0063] Group Depth(μm) ACP 17.56±4.17 PAMAM-COOH / ACMP 231.33±46.17 PAMAM-COOH / ACMP-MDP 229.29±63.46
[0064] Since no obvious mineral deposition was observed on the surface of the blank group and the MDP group, they were not included in the statistics. The results of pairwise comparison showed that the average penetration depth of the PAMAM-COOH / ACMP group and the PAMAM-COOH / ACMP-MDP group into the dentinal tubules was greater than that of the ACMP group (P<0.001), and the difference was statistically significant.
[0065] Experiment (2): Scanning electron microscopy and transmission electron microscopy were used to evaluate the remineralization effect of mineralization induction on completely demineralized human dentin slices. According to the grouping, 5 tooth slices were divided into each group. Each tooth was immersed in 0.5 ml of each solution filtered by a 0.22 um needle filter. After incubation in a constant temperature box at 37°C and 100% humidity for 7 days, the dentin slices were taken out, rinsed with deionized water for 30 seconds, and then stored in deionized water for testing. Scanning electron microscopy and transmission electron microscopy were performed respectively. Scanning electron microscopy detection: After the dentin was taken out from the deionized water, it was gradient dehydrated, critical point dried, and gold sprayed. The surface morphology of human dentin collagen fibers was observed using a scanning electron microscope at an accelerating voltage of 5 kV. Transmission electron microscopy detection: The dentin slices were immersed in electron microscope fixative, fixed at room temperature in the dark for 2 hours, and then transferred to 4°C for storage in the dark. The longitudinal section was cut from the middle to prepare ultrathin sections, and the remineralization of human dentin collagen fibers was observed at an accelerating voltage of 80 kV.
[0066] The scanning electron microscopy results are as follows Figure 8As shown in the figure, the blank control group: the collagen fibers were not mineralized, the fibers were thin, and the gaps between the fibers were large (arrows). The ACP group: the collagen fibers at the mouth of the dentinal tubules were mineralized, and the mineralization was limited to the surface of the collagen fiber network (arrows in B2 and B3). The collagen fibers became thicker and the gaps became smaller, but the collagen fibers in the deep part of the tubules did not have segmental thickening and mineralization was not obvious (as shown in Figure B4). The MDP group: a membranous adhesion layer appeared on the surface of the surface collagen fiber network (arrows), and the collagen fiber network below the membranous layer did not show mineralization. The PAMAM-COOH / ACMP group and the PAMAM-COOH / ACMP-MDP group: obvious characteristics of collagen fiber mineralization can be seen in the surface and deep dentinal tubules. The collagen fibers were thicker than those in the blank control group and mineralized and connected into sheets. The gaps between the fibers became smaller (arrows), and the gaps between the fibers in the PAMAM-COOH / ACMP-MDP group were smaller than those in the PAMAM-COOH / ACMP group. Compared with the control groups, after the mineralization induction of PAMAM-COOH / ACMP-MDP ethanol solution, obvious characteristics of collagen fiber mineralization can be seen on the surface of the dentin and in the deep dentin tubules. The fibers become segmentally coarser and mineralized into sheets, and the gaps between the fibers become smaller. Fig. 9 As shown in the figure, no dark-stained mineral particles were observed in the collagen fibers of the blank group, ACP group, and MDP group. In the PAMAM-COOH / ACMP group and PAMAM-COOH / ACMP-MDP group, obvious mineralization characteristics of collagen fibers inside and outside the peritubular dentin were observed. Dark-stained mineral particles were densely arranged along the longitudinal direction of the fibers (arrows), indicating that after mineralization induction with PAMAM-COOH / ACMP-MDP ethanol solution, obvious mineralization characteristics of collagen fibers inside and outside the peritubular dentin were observed. Fig.10 The results showed that the characteristic periodic horizontal stripes of collagen fibers after mineralization with PAMAM-COOH / ACMP-MDP ethanol solution disappeared, dark-stained mineral particles were densely arranged along the longitudinal direction of the fibers, and mineral deposition was visible outside the fibers. These results all indicate that the magnesium-carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite has a good ability to induce remineralization of demineralized dentin.
[0067] 3. Test on the effect of self-etched dentin bonding interface strength and durability
[0068] The effect of PAMAM-COOH / ACMP-MDP ethanol solution as an additional primer on the strength and durability of the self-etched dentin bonding interface was evaluated.
[0069] The experimental groups were blank control group (resin bonding was performed on the ex vivo dentin slices according to the clinical operation routine), ACP group (amorphous calcium phosphate powder was added to 50 vol% ethanol solution to prepare an ACP ethanol solution with a concentration of 3 mg / mL. Before bonding, a small amount was applied to the dentin bonding surface with a small cotton swab for 20 seconds, and then dried with an air gun and then bonded with resin according to the steps of the blank group), and MDP group (MDP solid was added to 50 vol% ethanol solution to prepare an MDP ethanol solution with a concentration of 3 mmol / L. Before bonding, a small amount was applied to the dentin bonding surface with a small cotton swab for 20 seconds, and then dried with an air gun and then bonded with resin according to the steps of the blank group). The blank group (PAMAM-COOH / ACMP group) (PAMAM-COOH / ACMP ethanol solution synthesized according to the method of Comparative Example 1, a small amount of which was applied to the dentin bonding surface with a small cotton swab for 20 seconds before bonding, and then dried with an air gun and then bonded with the resin according to the steps of the blank group) and the PAMAM-COOH / ACMP-MDP group (PAMAM-COOH / ACMP-MDP ethanol solution synthesized according to the method of Example 1, a small amount of which was applied to the dentin bonding surface with a small cotton swab for 20 seconds before bonding, and then dried with an air gun and then bonded with the resin according to the steps of the blank group).
[0070] After the bonding of the above experimental groups was completed, the dentin slices were immersed in 37℃ deionized water for 24h, and then the shear strength of the immediate group was tested first; after the test, the specimens were placed in a hot and cold cycler, the temperature of the cold water bath was set to 5℃, and the temperature of the hot water bath was set to 55℃. Each cycle of hot and cold baths was 30s each, and a total of 10,000 cycles were performed. After the hot and cold cycles were completed, the shear strength of the aging group of the specimens was tested after aging. The shear strength was tested by a computer-controlled universal mechanical testing machine. A special fixture was used to fix the bonding specimen. The loading head was close to the bonding surface. The loading force was parallel to the bonding surface. The loading speed was 0.5mm / min until the resin block broke and fell off. The peak load required to separate the cylinder from the tooth surface was divided by the bonding surface area, and the following formula was used to record the micro-shear bonding strength: bonding strength (P) = peak load (Fmax) / bonding area (S). The shear strength was measured in MPa.
[0071] The experimental results are shown in Table 2: The average shear strength of the PAMAM-COOH / ACMP-MDP group is 6.53±3.91MPa (immediately after bonding) and 5.24±2.79MPa (after aging), which are higher than those of other control groups, and the difference is statistically significant (P<0.05). It proves that the PAMAM-COOH / ACMP-MDP ethanol solution as an additional primer can improve the immediate bonding strength and the bonding strength after aging of the resin adhesive, and enhance its anti-aging property.
[0072] Table 2 Shear strength test results
[0073]
Claims
1. A method for preparing a carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite, characterized in that The following steps are involved: (1) Mixing the carboxylated polyamide-amine aqueous solution and the soluble magnesium salt aqueous solution, letting them stand for 4 to 10 hours, adding the soluble calcium salt, continuing to mix, letting them stand for 4 to 10 hours, and then adding anhydrous ethanol, or anhydrous ethanol and distilled water, to obtain an ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium; (2) dissolving decyl methacrylate phosphate in an ethanol solution, adding a phosphoric acid solution or a soluble phosphate solution, and mixing well to obtain a phosphorus solution; (3) Evenly mix the ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium with the phosphorus solution, wherein the molar ratio of calcium ion to phosphate ion is 2 to 1:1, and stir or shake the mixture for 20 to 60 minutes to obtain a polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite.
2. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: In the ethanol mixed solution containing magnesium, carboxylated polyamide-amine and amorphous calcium, the concentration of carboxylated polyamide-amine is 0.10-1.50 mmol / L, and the concentration of Mg is 0.10-1.50 mmol / L. 2+ The concentration of Ca is 0.05~0.50 mmol / L, 2+ The concentration is 1~20 mmol / L.
3. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: In the ethanol mixed solution containing magnesium, carboxylated polyamide-amine and amorphous calcium, carboxylated polyamide-amine, Mg 2+ , Ca 2+ The molar ratio is 0.5~5:1:20~50.
4. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: The volume percentage of ethanol in the ethanol mixed solution containing magnesium, carboxylated polyamide-amine and amorphous calcium and / or in the phosphorus solution is 40-60%.
5. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: In the phosphorus solution, PO4 3- The concentration of is 0.5~12.0 mmol / L, and the concentration of decyl methacrylate phosphate is 0.5~12.0 mmol / L.
6. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: In the phosphorus solution, decyl methacrylate phosphate and PO4 3- The molar ratio is 1~10:1~10.
7. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: In step (3), the reaction temperature is 8-15°C.
8. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: Step (1) is specifically as follows: 0.8-12 mmol / L of a carboxylated polyamide-amine aqueous solution and 10-100 mmol / L of a magnesium chloride aqueous solution are vortex-mixed at a volume ratio of 15-35:1, and allowed to stand for 4-10 hours. Then, 30-50 times the volume of the magnesium chloride aqueous solution and 10-100 mmol / L of a calcium chloride aqueous solution are added, and vortex-mixed, and allowed to stand for 4-10 hours. Then, 30-50 times the volume of the magnesium chloride aqueous solution and 80-120 times the volume of the magnesium chloride aqueous solution are added, and anhydrous ethanol is added, and vortex-mixed to obtain an ethanol mixture containing magnesium, carboxylated polyamide-amine and amorphous calcium.
9. The method for preparing the carboxylated polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to claim 1, characterized in that: Step (2) is specifically as follows: preparing 0.5-13.0 mmol / L of 40-60 vol% ethanol solution of decyl methacrylate phosphate, adding concentrated phosphoric acid to make the concentration of phosphoric acid 0.5-12.0 mmol / L, vortex mixing, and obtaining the phosphorus solution.
10. Application of the preparation method of the polyamide-amine / amorphous calcium phosphate-methacrylate decyl phosphate nanocomposite according to any one of claims 1 to 9 in inducing biomimetic mineralization of collagen fibers and resin bonding.
Citation Information
Patent Citations
Nano-composite capable of inducing collagen fiber bionic internal mineralization and preparation method of nano-composite
CN112999094A
Carboxylated polyamidoamine-amorphous calcium phosphate micelle as well as preparation method and application thereof
CN116120589A
Dental curable composition, and dental material using the same
JP2012077009A
